Employee career decision making: the influence of salary and benefits, work environment and job security / Nur`ain Achim, Nur Idayu Badrolhisam and Nurfitriah Zulkipli - Achim, Nur`ain; Badrolhisam, Nur Idayu; Zulkipli, Nurfitriah (Universiti Teknologi MARA, Negeri Sembilan, 2019)
Every individual at some point will make critical career decision making in life. Making a wrong career decision will affect a person’s future including feeling unhappy, job stress and eventually job withdrawal. This study examined the factors affecting career decision making among government servants in Malaysia. The population and sample were taken from three departments. The population was 140 employees and 103 respondents were identified as the sample. Convenience sampling was employed to collect the primary data. The result from several statistical analysis found that all the independent variables; salary and benefits, working environment and job security were correlated with the dependent variable that is career decision making. Therefore, from the findings, employers, especially from the government agencies, were urged to increase recruiting permanent position instead of contract employment and offering better benefits to improve employees’ career decision making.